Public administration research in East and Southeast Asia: A review of the English language evidence, 1999-2009 - Walker, Richard M.; Choi, Yujin; Brewer, Gene A. (2014)
In this article, we describe and explore the topics, methods, and author arrangements of the English language literature on public administration in East and Southeast Asia. Articles in the review are for the period 1999-2009 and were identified in the Web of Science. Searches identified 309 articles in the disciplinary area of public administration. The emphasis of scholarly attention is on East Asia China, Japan, Hong Kong, Taiwan, and South Korea. Four major characteristics of this literature are noted. First, it is comparative in nature. Second, it focuses on system and regime change, as well as policies, as the major topics and units of analysis. Thirdly, it is primarily based on normative argumentation, and where it is empirical, it typically relies on secondary data. Fourth, it is largely interdisciplinary in nature, drawing on many disciplines and scholars from around the globe, but it is dominated by scholars based in English language speaking countries. In conclusion, we discuss the implications of these findings for the public administration discipline and research in the region. - Reproduced.
Keywords: Research; Public administration